The Settlement of Sharia Banking Dispute based on Legal Culture as a Practice of Indonesian Islamic Moderation - Erie Hariyanto (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2019)
Islamic banking and religious courts have a very close-knit network. Both Islamic banking serving as Islamic financial intermediation institution and religious courts as special courts with authority to resolve the dispute of  Islamic banking similarly stressed on applying the sharia principles in the operation. They are expected to sinergically rely on sharia principles. The philosophical basic of religious courts’ authority  in dispute settlement of shariah banking  is to create a harmony between the execution of contract and material law based on the principles of sharia with religious courts as an institutiton for Moslem justice-seekers so that the disputes can be resolved wholly (kafa’ah) and consistently (istiqomah) through court rulings upholding the culture of law. The meeting of values of sharia and culture living in society produces harmony in terms of Islamic banking dispute settlement. (Keberadaan Perbankan Syariah dan Peradilan Agama memiliki keterkaitan yang sangat erat. Perbankan Syariah sebagai lembaga intermediasi keuangan syariah dan Peradilan Agama sebagai lembaga peradilan khusus yang mempunyai kewenangan ablosut menyelesaikan sengketa perbankan syariah sama-sama menekankan menerapkan prinsip-prinsip syariah dalam operasionalnya. Perbankan Syariah dan peradilan agama diharapkan dapat bersinergis dengan berpegang pada prinsip syariah. Dasar filosofis Kewenangan Peradilan Agama dalam Penyelesaian sengketa perbankan syari’ah adalah agar terciptanya keselarasan antara pelaksanaan akad dan hukum materiil yang berlandaskan prinsip-prinsip syariah dengan lembaga peradilan agama yang memang merupakan wadah bagi pencari keadilan yang beragama islam sehingga sengketa perbankan syariah dapat diselesaikan secara kafaah dan istiqomah melalui putusan pengadilan yang mengedepankan budaya hukum. Pertemuan nilai syariah dan budaya yang hidup dalam masyarakat menghasilkan harmoni dalam penyelesaian sengketa perbankan syariah)